Water, cacao, and the early Maya of Chocolá - Kaplan, Jonathan 1947-; Paredes-Umaña, Federico (University Press of Florida, 2018)
In describing what was, in effect, a lost Maya city, the book highlights the many important research findings to date of long-term field research at the city, including a very early, yet extraordinarily sophisticated ancient water control system, and evidence for cacao arboriculture, to explain its rise to wealth and power as a "kingdom of chocolate"; also detailed are the ancient city's sculpture and ceramics and the ethnohistory of the modern Maya community lying atop it